Hubungan Sikap Perawat dengan Tingkat Kepuasan Pasien Rawat Inap di PKU Muhammadiyah Yogyakarta - ABILANG, Fakhirah Meyana H (STIKES 'Aisyiyah Yogyakarta, 2009)
Success of hospital to improve service quality greatly related to patient’s satisfaction. Satisfaction rises from first sight in patient who submits based on nursing service. Though one who existed in hospital succeed in medical academy of treating patient, but if their attitude was not good, all done could be said fail to serve the patient. This study was to know whether there was relationship between nurse’s attitude and satisfaction of hospitalized patient at general hospital PKU Muhammadiyah Yogyakarta. Data collection was done from may until July 2009, with descriptive research design of correlation and cross sectional approach. Sample taken used Purposive Sampling technique with 97 respondents. Validity test used Content validity index (CVI) with result of 0,888 in nurse’s attitude and 0,875 in patient’s satisfaction. Reliability test used Cronbach alfa formulation with result of 0,941 in nurse’s attitude and 0,688 in patient’s satisfaction. Hypothesis was applied with Pearson product moment correlation. Result of the research indicated that there was statistically significant relationship between nurse’s attitude and satisfaction of hospitalized patient at general hospital PKU Muhammadiyah Yogyakarta (r=0,402; p?0,01). It was expected that hospital management could improve quality of human resource in nurse by way to give training or seminal from all nurses concerning and how nurse should have attitude in front of patient, so that they could improve patient’s satisfaction on hospital service